Toward a Theoretical Framework of Relationship Marketing in the Business Context - Kawsar Ahmmed; Shahidul Islam; Nor Azila Mohd. Noor; Khandoker Mahmudur Rahman; Fizar Ahmed (Tržište, 2019)
Purpose – This paper addresses the issues related to the practice of relationship marketing at the organizational level. Considering the influence of various factors, this study offers a theoretical framework necessary to create, maintain, and enhance the business relationship. Design/methodology/approach – The research is based on a systematic review of existing literature, including journal articles, subject-specific professional websites, and textbooks on relationship marketing. Literature reviews relating to the Nordic School, Industrial Marketing and Purchasing (IMP) Group Approach, and the North American School are included. Findings – The relationship marketing approach has evolved since the pre-industrial era, and more organizations are embracing this marketing stance in the current, post-industrial era. A theoretical framework that consists of influential variables for creating, maintaining, and enhancing relationships is proposed to explore this multidimensional construct. Information on proper conditions is synthesized to help marketers identify an appropriate environment for implementing this approach in the business context. Limitations – Given the increasing complexity of relationship marketing and the increasing need to understand this approach, the proposed theoretical framework could be useful for improving the understanding of multi-dimensional aspects of relationship marketing. Consequently, directions for future research in relationship marketing are identified. Originality/value – This study provides a coherent picture of relationship marketing viewed through the proposed theoretical framework, based on a systematic literature review. Specifi cally, it is probably a first instance in which a paper sought to address the practice of relationship marketing by including tripartite areas – namely, creating, maintaining, and enhancing relationships in a Business to Business (B2B) setting, which is scattered across various disciplines.